An Evaluation of Noise Pollution Level in Lucknow city, Uttar Pradesh - Srivastava, Shweta (National Geographical Journal of India, 2022)
Noise is generally defined as the unwanted sound produced by various natural or man-made sources such as construction, industrial, transportation activities etc. Noise can have many adverse effects such as hearing impairment, sleep disturbance, interference with speech and communication, reduced performance, annoyance and harming physiological functions. In India, the permissible noise level for different areas is laid down by Central Pollution Control Board (CPCB). Lucknow city, one of the major urban centres of Uttar Pradesh, has a population around 28 lakh according to Census, 2011. This huge number of people contributes significantly in the increasing levels of noise and, therefore, creates an alarming state of noise pollution. This paper aims to study the growing noise level trends in the city, analyse the average sound levels to ascertain the status of ambient noise levels and recommend suitable preventive measures. The data used for substantiation has been drawn from the reports of Central Pollution Control Board (CPCB) and Uttar Pradesh Pollution Control Board (UPPCB). Microsoft Excel software has been used for tabulation and graphical representation of data while ArcGIS 10.3 software has been used for the cartographical representation